Pengaruh Profitabilitas Dan Kepemilikan Institusional Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2014 - Aditya, Dinda; Supriyono, Edi (Jurnal Manajemen Bisnis, 2015)
The main purpose of this study is to empirically analyze the influence of Profitability and Institutional Ownership to Firm Value with Dividend Policy as an intervening variable. The sample of the study consisted of manufacture companies which are listed on the Indonesian Stock Exchange period 2010-2014 and selected based on the purposive sampling. The data of the study from secondary sources by using documentation record. The analysis was conducted by using classic assumption testing consisting of heteroscedasticity testing, multicoliniearity testing and autocorelation testing. The hypotesis was tested by using multiple linear regression.The result proved that the Profitability (Return on Asset) and Dividend Policy (Dividend Payout Ratio) are positive and significant to Firm Value (Price to book value). The Institutional Ownership (INST) does not significant to Firm Value (Price to Book Value). The Profitability (Return on Asset) does not significant to Dividend Policy (Dividend Payout Ratio). The Institutional Ownership (INST) is positive and significant to Dividend Policy (Dividend Payout Ratio). Profitability (Return on Asset) does not significant to Firm Value with Dividend Policy (Dividend payout ratio) as intervening variable. The Institutional Ownership (INST) is positive and significant to Firm Value (Price to book value) with Dividend Policy (Dividend Payout Ratio) as intervening variable.